THE EFFECT OF SUPERVITA M PREMIX ON THE PRODUCTIVITY OF CHICKENS (Journal of Multidisciplinary Sciences and Innovations, 2026)
The poultry industry plays a crucial role in ensuring food security by providing high-quality protein sources such as meat and eggs. Optimizing poultry productivity requires balanced nutrition, including adequate levels of vitamins, minerals, and biologically active substances. Premixes have become an essential component of modern poultry feeding strategies, as they help prevent nutrient deficiencies and enhance growth performance and reproductive efficiency. Supervita M is a multicomponent vitamin-mineral premix formulated to improve metabolic processes, immune function, and productivity in poultry.The present study aimed to evaluate the effect of Supervita M premix on the productivity, growth performance, feed efficiency, egg production parameters, and health status of chickens. The study was conducted under controlled experimental conditions using two groups of chickens: a control group fed a standard basal diet and an experimental group receiving the same diet supplemented with Supervita M premix. Parameters such as body weight gain, feed conversion ratio, egg production rate, egg quality indicators, and general health status were assessed over a defined experimental period.The results demonstrated that supplementation with Supervita M premix significantly improved growth performance, feed utilization, and egg production compared to the control group. Chickens receiving the premix showed enhanced immune resistance and better overall physiological condition. These findings indicate that Supervita M premix is an effective nutritional supplement for improving poultry productivity and can be recommended for use in commercial poultry farming.